Systematic revision of Late Triassic marine gastropods from Central Perú: considerations on the Late Triassic/Early Jurassic faunal turnover - Ferrari, Silvia Mariel (2015)
The Late Triassic/Early Jurassic boundary is marked by a mass extinction event which had an important effect on the marine benthic communities on a global scale. In the Andean region of South America, however, the impact of this phenomenon on the earliest Mesozoic marine invertebrate associations has not been evaluated thus far. The present contribution is a systematic revision of the Late Triassic marine benthic gastropod faunas from the Pucará Group of Central Perú, giving a detailed characterization of 18 species and an updated systematic assigment of representatives of the genera Chartroniella, Phymatifer, Ptychomphalina, Paracerithium, Rhabdocolpus and Omphaloptycha. This research includes a comparison of the Peruvian fauna with their related counterparts from the Early Jurassic of Argentina and the Early/Middle Jurassic of New Zealand. This approach attempts to interpret the Late Triassic/Early Jurassic faunal turnover after the end Triassic crisis and establishes a palaeobiogeographical scheme for the gastropod faunal exchange in the Southern Hemisphere across the palaeo-Pacific seaway during the Late Triassic/Early Jurassic.